Ideology at Face Value: The Stars of Postwar Japanese Cinema and Their Representation Strategies in the Press (1945-1952) - FedorovaAnastasia Aleksandrovna (Communications. Media. Design, 2022)
After the defeat in World War II, Japan lost its political sovereignty and was occupied by the American troops. During these years, film was employed for propaganda purposes. Cinema illustrated the changes embraced by postwar Japan and also served as their catalyst, offering the viewers with new models of interacting with reality. Japanese film stars set a powerful example to follow. By analyzing the representation strategies of female stars, whose popularity peaked during the years of occupation, this paper examines the role of media in building Japan’s new cultural identity. By examining the images Kyo Machiko (1924–2019) and Hara Setsuko (1920–1915) in film and printed media, as well as the historical context surrounding the promotion and reception of these popular actresses, the paper argues that the overtly “feminized” image of postwar Japan compelled the audience to look for an alternative — a vision of an idealized woman who could challenge the stereotype of a “passive” and “subordinate” female. Both Hara Setsuko and Kyo Machiko in their own way contributed to mending the wounded feelings of patriotism and mitigating the psychological frustration experienced by postwar Japanese audiences.